Pemanfaatan Instrumen Derivatif Di Indonesia Dan Perbandingan Standar Akuntansi Terkait Derivatif - Niansyah, Fitri Irka Wahyu; Indriana, Putri; Firmansyah, Amrie (Institut Bisnis dan Informatika Kesatuan, 2018)
The purpose of this study is to discuss the usage of derivative instruments in Indonesia and to compare the Indonesia Financial Accounting Standards and International Financial Reporting Standards (IFRS) as well as the United State Generally Accepted Accounting Principles (US GAAP).. The method used in this research is qualitative method with descriptive approach and general comparative study. The aspects to be analyzed are the actual condition of the usage of derivative instruments in Indonesia and the main differences between recognition and measurement of derivative instruments under said accounting standards. The results of this study suggests the development of Indonesia derivatives market is still slow and not as advanced as other countries in Asia, like Korea and Malaysia, although the use of derivative instruments shows an increasing trend when viewed from the volume of transactions each year, but. Also, the comparison of accounting standards covering the accounting treatment for derivative instruments suggests that Indonesia Financial Accounting Standards is very closely aligned with IAS 39 provision eventhough there have been several amendments made to IAS 39. However, the main difference between IFRS and US GAAP is related to the hedge accounting in connection with risk components.